Asceza, akrobacja, aleturgia. O konwersji w literaturze - Bielawa, Jacek (Przestrzenie Teorii, 2022)
Using the concepts of Michel Foucault’s technologies of the Self and Peter Sloterdijk’s anthropotechnics, the article attempts to create a theoretical model of literature as a tool for converting a literary subject. This model distinguishes three forms of the Self that are revealed in the process of conversion carried out in the medium of literature: the Self as subject, the Self as object and the other Self. Within the relations between these three incarnations, three conversion processes have been distinguished: asceticism – understood as an exercise in writing, acrobatics – as an act of literary secession to another world, and alethurgy – a textual technique of self-knowledge. Ultimately, this theoretical model is presented in the form of a conversion triangle.